(untitled) (Canadian Medical Education Journal, 2015)
Background: Health advocacy is currently a key component of medical education in North America. In Canada, Health Advocate is one of the seven roles included in the Royal College of Physicians and Surgeons of Canada’s CanMEDS competency framework. Method: A literature search was undertaken to determine the current state of health advocacy in Canadian postgraduate medical education and to identify issues facing educators and learners with regards to health advocacy training. Results: The literature revealed that the Health Advocate role is considered among the least relevant to clinical practice by educators and learners and among the most challenging to teach and assess. Furthermore learners feel their educational needs are not being met in this area. A number of key barriers affecting health advocacy education were identified including limited published material on the subject, lack of clarity within the role, insufficient explicit role modeling in practice, and lack of a gold standard for assessment. Health advocacy is defined and its importance to medical practice is highlighted, using pediatric emergency medicine as an example. Conclusions: Increased published literature and awareness of the role, along with integration of the new 2015 CanMEDS framework, are important going forward to address concerns regarding the quality of postgraduate health advocacy education in Canada.